Assessment of the efficacy and safety of 30% supramolecular salicylic acid peeling for papulopustular rosacea treatment - Linghui Xu; Boxin Yao; Tianxing Xu; Huang Huang (Indian Journal of Dermatology, 2022)
Background: Thirty per cent supramolecular salicylic acid (SSA) is a water-soluble, sustained release salicylic acid (SA) modality, which is well tolerated by sensitive skin. Anti-inflammatory therapy plays an important role in papulopustular rosacea (PPR) treatment. SSA at a 30% concentration has a natural antiinflammatory property. Aims: This study aims to investigate the efficacy and safety of 30% SSA peeling for PPR treatment. Methods: Sixty PPR patients were randomly divided into two groups: SSA group (30 cases) and control group (30 cases). Patients of the SSA group were treated with 30% SSA peeling three times every 3 weeks. Patients in both groups were instructed to topically apply 0.75% metronidazole gel twice daily. Transdermal water loss (TEWL), skin hydration and erythema index were assessed after 9 weeks. Results: Fifty-eight patients completed the study. The improvement of erythema index in the SSA group was significantly better than that in the control group. No significant difference was found in terms of TEWL between the two groups. The content of skin hydration in both the groups increased, but there was no statistical significance. No severe adverse events were observed in both the groups. Conclusion: SSA can significantly improve the erythema index and overall appearance of skin in rosacea patients. It has a good therapeutic effect, good tolerance and high safety.